Skype multimedia application traffic analysis on home Unifi network / Siti Fatimah Ramle - Ramle, Siti Fatimah (2017)
This research presents an analysis on Skype application network traffic collected using Wireshark applications tool. Skype being considered for traffic analysis because it is one of the most online video media applications used in today's network communication. Before, people communicate through Skype using telephone line where it is very costly. In today's broadband network called Unifi giving better bandwidth for Skype users and cheaper. However, it is important to determine whether the bandwidth offered by the Unifi is fully utilized by the users as they consistently pay for it. The main objectives of this research are to analyse Skype traffic characteristics such as usage of bandwidth, round trip time (RTT), and packet loss, Skype protocol, and Skype traffic model. The method involved establishing both video and voice calls at different time using Skype of home Unifi where one of the users runs the Wireshark to capture the traffic. Data are collected in schedule and analysed using MATLAB software. Collected data are analysed on total of bandwidth usage and type of protocol used. Comparison is being made between different protocols used in time. Then, Skype traffic model is identified by fitted the raw data. Two parameter Cumulative Distributions Functions (CDF) is generated. Maximum Likelihood Estimator (MLE) technique is used to get the best traffic model which presents the highest MLE value. Result presents that Skype is using UDP protocol more than TCP protocol and the bandwidth usage is underutilized where only 10% of bandwidth is used from the offered committed access rate paid on the access bandwidth line. This study is significant in developing a dynamic committed access rate algorithms line which would benefits the broadband network users.